Organization-Harm vs. Organization-Gain Ethical Issues: An Exploratory Examination of the Effects of Organizational Commitment - Cullinan, C. (Journal of business ethics, 2008)
The existing literature on the relationship between organizational commitment and ethical decision making suggests that ethical decision makers with higher organizational commitment are less likely to engage in ethically questionable behaviors. The ethical behaviors previously studied in an organizational commitment context have been organization-harm issues in which the organization was harmed and the individual benefited (e.g., overstating an expense report). There is another class of ethical issues in an organizational context, however. These other issues, termed organization-gain issues, focus on the organization obtaining a benefit while outsiders, such as investors, are harmed (e.g., overstating reported revenue). We explore whether individuals with higher organizational commitment are more or less likely to engage in questionable behaviors that benefit the organization. Results of our study indicate that individuals with higher organizational commitment are less likely to engage in ethically questionable behaviors, regardless of whether the behaviors are organization-harm or organizational-gain issues.